2019
DOI: 10.1136/thoraxjnl-2018-212994
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of microvesicle-containing miR-223/142 in lung inflammation

Abstract: BackgroundUncontrolled lung inflammation is one of the prominent features in the pathogenesis of lung infection- associated acute lung injury (ALI). Microvesicles (MVs) are extracellular nanovesicles that are generated via direct membrane budding.MethodsBronchoalveolar lavage fluid (BALF) samples were collected from mice with or without intratracheal lipopolysaccharide (LPS) instillation. BALF MVs were characterised and MV-containing microRNA (miRNA) profiles were assessed and confirmed. Secretion and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 38 publications
(44 reference statements)
3
116
0
Order By: Relevance
“…In 2007, EVs containing miRNAs (EV-miRNAs) and other noncoding RNAs were first discovered 14 . Interestingly, EV-miRNAs are suspected to be released during sterile and nonsterile lung damage in mice 6 , 8 , 9 , 25 and are significantly involved in the development of lung inflammation 6 , 25 . Studies in hyperoxia-associated oxidative stress have demonstrated a dramatic shift in EV-miRNA profiles in vivo after hyperoxia is induced 7 .…”
Section: Extracellular Vesicles In the Respiratory Systemmentioning
confidence: 99%
“…In 2007, EVs containing miRNAs (EV-miRNAs) and other noncoding RNAs were first discovered 14 . Interestingly, EV-miRNAs are suspected to be released during sterile and nonsterile lung damage in mice 6 , 8 , 9 , 25 and are significantly involved in the development of lung inflammation 6 , 25 . Studies in hyperoxia-associated oxidative stress have demonstrated a dramatic shift in EV-miRNA profiles in vivo after hyperoxia is induced 7 .…”
Section: Extracellular Vesicles In the Respiratory Systemmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity pneumonia in hospitals. In recent years, the incidence of Klebsiella pneumoniae has been on the rise [34,35]. Kidney transplant patients are typical immunocompromised hosts.…”
mentioning
confidence: 99%
“…Human ADAM15 cDNA (isoform 6 pre-proprotein as the longest transcript variant) amplified using RT-PCR was subcloned into the BamHI and XhoI sites of the pcDNA3.1 vector to obtain pcDNA- ADAM15 (the primer sequences used for cloning were: forward: 5′-CGCGGTACCATGCGGCTGGCGCTGCTCTGGG-3′; reverse: 5′-CCGCTCGAGTCAGAGGTAG-AGCGAGGACACT-3′). THP-1 cells (human monocyte-like cells; ATCC, Manassas, VA) were maintained in RPMI-1640 containing 10% fetal bovine serum and differentiated into macrophage-like cells by incubating them with 150 nM phorbol myristate acetate for 24 h. Cells were electroporated (Neon Transfection System; Thermo Fisher Scientific, Waltham, MA) with either the ADAM15 or the control (pcDNA3.1) vector [ 20 ]. ADAM15 expression was measured using quantitative RT RT-PCR and the THP-1 cells were treated with 5% CSE for up to 24 h. C-C motif chemokine ligand-2 (CCL-2), tumor necrosis factor-α (TNF-α), MMP-9, and MMP-12 levels were measured in the cell culture supernatants using ELISAs (R&D Systems, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%